Discovery of a PCAF Bromodomain Chemical Probe. Issue 3 (14th December 2016) - Moustakim, Moses; Clark, Peter G. K.; Trulli, Laura; Fuentes de Arriba, Angel L.; Ehebauer, Matthias T.; Chaikuad, Apirat; Murphy, Emma J.; Mendez‐Johnson, Jacqui; Daniels, Danette; Hou, Chun‐Feng D.; Lin, Yu‐Hui; Walker, John R.; et al.
Abstract: The p300/CBP‐associated factor (PCAF) and related GCN5 bromodomain‐containing lysine acetyl transferases are members of subfamily I of the bromodomain phylogenetic tree. Iterative cycles of rational inhibitor design and biophysical characterization led to the discovery of the triazolopthalazine‐based L‐45 (dubbed L‐Moses ) as the first potent, selective, and cell‐active PCAF bromodomain (Brd) inhibitor. Synthesis from readily available (1R, 2S)‐(−)‐norephedrine furnished L‐45 in enantiopure form. L‐45 was shown to disrupt PCAF‐Brd histone H3.3 interaction in cells using a nanoBRET assay, and a co‐crystal structure of L‐45 with the homologous Brd PfGCN5 from Plasmodium falciparum rationalizes the high selectivity for PCAF and GCN5 bromodomains. Compound L‐45 shows no observable cytotoxicity in peripheral blood mononuclear cells (PBMC), good cell‐permeability, and metabolic stability in human and mouse liver microsomes, supporting its potential for in vivo use. Abstract : Let my PCAF go : The first potent, selective, and cell‐active inhibitor of PCAF bromodomains (Brd) is reported. L ‐Moses was shown to disrupt the PCAF‐Brd/histone H3.3 interaction in cells using a nanoBRET assay, and a co‐crystal structure of L ‐Moses with the homologous Brd PfGCN5 helps explain the high selectivity for PCAF and GCN5 bromodomains.